AUTOMATION OF LAWMAKING: PROSPECTS FOR THE IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGY (Journal of actual problems of jurisprudence, 2025)
The foundation for this article is research and developments dedicated to the implementation of information and digital technologies in the legislative process to enhance its efficiency, transparency, and strengthen interactions between government authorities and citizens. The scientific novelty of the study lies in the application of advanced digital technologies to optimize legislative activities and expand civic participation in this process.The article explores the prospects for integrating artificial intelligence (AI) technologies into the legislative process, analyzing contemporary approaches to the automation of drafting, analyzing, and adapting regulatory legal acts. The article focuses on the application of natural language processing (NLP), machine learning, and expert systems to enhance the efficiency and accuracy of law-making processes.The authors conduct a comparative analysis of the experience of digitalization of lawmaking in different countries, focusing on the potential risks and legal challenges associated with the use of artificial intelligence technologies in this area. It is noted that AI is already being used in certain elements of legislative activity, but mainly as an auxiliary tool rather than an independent participant in the process. Based on the results of the study, it was concluded that the automation of lawmaking using AI is highly promising. Its use is particularly in demand at the stages of information analysis, preparation of draft laws and assessment of regulatory impact. At the same time, the need to develop regulatory, ethical, and procedural frameworks for the safe and effective integration of AI into lawmaking is emphasized.The conclusion offers recommendations for integrating intelligent systems into Kazakhstan’s legislative process and outlines possible directions for further research.Keywords: lawmaking, artificial intelligence, research study, prospects, efficiency.